2009
DOI: 10.1037/a0014493
|View full text |Cite
|
Sign up to set email alerts
|

Motivationally significant stimuli show visual prior entry: Evidence for attentional capture.

Abstract: Previous studies that have found attentional capture effects for stimuli of motivational significance do not directly measure initial attentional deployment, leaving it unclear to what extent these items produce attentional capture. Visual prior entry, as measured by temporal order judgments (TOJs), rests on the premise that allocated attention accelerates perception, that is, stimuli that receive attention first are perceived first; thus, this method is a sensitive and direct measure of the time course of ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
99
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(111 citation statements)
references
References 67 publications
(137 reference statements)
6
99
5
Order By: Relevance
“…Very few studies have been able to provide evidence in support of rapid orienting to threat (Stein, Seymour, Hebart, & Sterzer, 2014;West, Anderson, & Pratt, 2009). Delays in attentional disengagement have been observed more readily, mainly in studies employing the dot-probe paradigm with a neutral baseline (Fox, Russo, & Dutton, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Very few studies have been able to provide evidence in support of rapid orienting to threat (Stein, Seymour, Hebart, & Sterzer, 2014;West, Anderson, & Pratt, 2009). Delays in attentional disengagement have been observed more readily, mainly in studies employing the dot-probe paradigm with a neutral baseline (Fox, Russo, & Dutton, 2002).…”
mentioning
confidence: 99%
“…An organism's odds of survival can be increased by focusing the limited-capacity processing resources of the visual system on potential threats in the environment (Öhman & Mineka, 2001;Tamietto & De Gelder, 2010;West, Anderson, & Pratt, 2009). For example, if a visual scene contained both a potentially poisonous spider and a harmless butterfly, orienting attention to the spider would facilitate its processing and allow us to take appropriate actions.…”
mentioning
confidence: 99%
“…If faces are presented, those posing a threatening emotional expression have stronger effects on attentional capture or hold in non-clinical samples (e.g. Mogg & Bradley, 1999;Milders, et al, 2006;Li, et al, 2007;Carlson, Reinke, & Habib, 2009;West, Anderson, & Pratt, 2009). …”
mentioning
confidence: 99%
“…Studies in cognitive psychology have shown that the deployment of attentional resources (Kahneman, 1973;Matthews & Desmond, 1998) is determined by various external factors, such as physically (Theeuwes, 2010) and socially (West, Anderson, & Pratt, 2009) distinctive items, as well as by endogenous factors, such as intention (Hommel, 2010). Moreover, the deployment of attention can also be affected by such internal factors as motivation (Della Libera & Chelazzi, 2006) and the current mood state (Fredrickson, 2004;Friedman & Forster, 2010), because the internal states of observers can influence executive function (Ashby, Isen, & Turken, 1999), which governs the major cognitive systems, thereby including the deployment of attention.…”
mentioning
confidence: 99%